Reproduction of assimilationist thinking in Norwegian social studies: Breaking the cycle through reflective practice - Skotnes, Christian Engen; Ringrose, Priscilla (JSSE - Journal of Social Science Education, 2024)
Highlights: We have learned that we, as teachers and teacher educators, need to be aware of the risk of reproducing uncritical approaches in educational interventions on migration. Without crucially reflecting on their own practice, even social studies teachers dedicated to anti-racist thinking risk reproducing assimilationist values. The article argues that this risk can be mitigated when teachers critically evaluate their own practice as a precondition for facilitating transformative learning in their students. Purpose: The article aims to critically reflect on a classroom situation where we, as upper secondary social studies teachers, were complicit in reproducing and soliciting assimilationist values in a student assignment. Design/methodology/approach: We use a critical reflective model to 1) reflect on our discomfort at this complicity, 2) analyse the assimilationist values reproduced, and 3) redesign the assignment to promote inclusive citizenship. Findings: The article exposes the risk and potential of being vulnerable about our practice as teachers and of opening the classroom as a safe space for critical thinking. Research limitations/implications: More research is needed on how social studies teachers understand integration and how they (re)design their own assignments. Practical implications: Without crucially reflecting on their own practice, even social studies teachers dedicated to anti-racist thinking risk reproducing assimilationist values. This risk can be mitigated when teachers critically evaluate their own practice as a precondition for facilitating transformative learning in their students.